Effect of pesticides on Beauveria bassiana and gut microbiota used in biorational methods for the control of Anastrepha obliqua (Diptera: Tephritidae) - Sánchez, Daniel; Campollo-Ovalle, Augusto; Rodas-Hilerio, Luis Fernando; Solórzano-Gordillo, Erik de Jesús (Revista Colombiana de Entomología, 2024)
The implementation of microorganism-based control methods aims to ameliorate the harm caused by pests while simultaneously reducing the unwanted effects caused by synthetic pesticides. However, the interaction between biorational and conventional methods might cause a reciprocal reduction in the efficacy of both methods. Some studies report that pesticides may cause reductions in the pathogenicity of Beauveria bassiana strains and changes in the gut microbiome of some insect species. This is important because B. bassiana is used for fruit fly control, and gut microbiome is known to influence the quality of males reared for autocidal control. The aim of this work was to analyze the toxicity of the herbicide glyphosate and some insecticides on microorganisms used in the control of the fruit fly, Anastrepha obliqua: (1) the entomopathogenic fungus Beauveria bassiana, and (2) the gut microbiome of males of A. obliqua. The results showed that none of the pesticides caused acute toxicity on the evaluated microorganisms. Even though these results suggest that integrating these microorganisms under the current usage of the evaluated pesticides here is feasible, it is relevant to acknowledge that many other environmental variables might be involved. Therefore, field studies are required to complement the findings of this study.